2017
DOI: 10.1111/mec.14441
|View full text |Cite
|
Sign up to set email alerts
|

Pleistocene climatic changes drive diversification across a tropical savanna

Abstract: Spatial responses of species to past climate change depend on both intrinsic traits (climatic niche breadth, dispersal rates) and the scale of climatic fluctuations across the landscape. New capabilities in generating and analysing population genomic data, along with spatial modelling, have unleashed our capacity to infer how past climate changes have shaped populations, and by extension, complex communities. Combining these approaches, we uncover lineage diversity across four codistributed lizards from the Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 90 publications
0
52
0
Order By: Relevance
“…Australia underwent significant climatic oscillations throughout the Pliocene and Pleistocene (Byrne et al., , ), affecting traits, distributions, and diversification of contemporary species (Potter et al. ). During this time, species in the Pseudomys Division repeatedly colonized the expanding and contracting arid, monsoon, and mesic biomes (Smissen and Rowe ), and the optimum body size of species in the Pseudomys Division shifted in response to these transitions, resulting in a high λ value.…”
Section: Discussionmentioning
confidence: 99%
“…Australia underwent significant climatic oscillations throughout the Pliocene and Pleistocene (Byrne et al., , ), affecting traits, distributions, and diversification of contemporary species (Potter et al. ). During this time, species in the Pseudomys Division repeatedly colonized the expanding and contracting arid, monsoon, and mesic biomes (Smissen and Rowe ), and the optimum body size of species in the Pseudomys Division shifted in response to these transitions, resulting in a high λ value.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was considerable variation in the direction and timing of change in both temperature and precipitation across the MT (Reeves et al, ) and some of the most mesic areas (e.g. northern Top End) could have been much less affected by the LGM (Potter et al, ). For the AZ, the obvious major refugia are the ancient rocky ranges and plateaus of the Pilbara craton in the west and the Central Ranges in the inland (Figure ; Oliver & McDonald, ; Pepper, Doughty, & Keogh, ; Pepper, Fujita, Moritz, & Keogh, ; Pepper, Ho, Fujita, & Keogh, ).…”
Section: Introductionmentioning
confidence: 99%
“…For the AZ, the obvious major refugia are the ancient rocky ranges and plateaus of the Pilbara craton in the west and the Central Ranges in the inland (Figure ; Oliver & McDonald, ; Pepper, Doughty, & Keogh, ; Pepper, Fujita, Moritz, & Keogh, ; Pepper, Ho, Fujita, & Keogh, ). For the MT, major refugia occur in the dissected sandstone plateaus and ranges in the Top End and Kimberley (Potter, Eldridge, Taggart, & Cooper, ; Potter et al, ), as well as karst limestones at the interface of the AZ and MT (Oliver et al, ). Each of these MT refugia has high endemism, and thus, conservation value (Rosauer et al, , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, genetic analysis of reptiles, a rich and geographically structured AMT faunal group [14], has repeatedly demonstrated that snake [15], gecko [16][17][18] and skink [19,20] taxa previously considered to be widespread species actually represent diverse complexes of genetically and often also morphologically differentiated taxa, Diversity 2018, 10, 36; doi:10.3390/d10020036…”
Section: Introductionmentioning
confidence: 99%